Late‐onset asystole associated with vagal nerve stimulation - Divya Nagabushana; Huan Huynh; Mark D. McCauley; Anna Serafini (Epilepsia Open)
Abstract Vagal nerve stimulation (VNS) is a form of neuromodulation that is an established adjunct in the management of drug‐resistant epilepsy. The common side effects of VNS are cough, dysphonia, or shortness of breath, which are often mild and do not require discontinuation of therapy. However, serious adverse effects such as bradyarrhythmia and asystole can occur rarely in patients who have had VNS implanted several years ago due to certain technical issues, patient‐related risk factors, and unknown causes that necessitate the deactivation of VNS. We describe the late onset of bradyarrhythmia in a 32‐year‐old patient with drug‐resistant epilepsy 2 years after the implantation of VNS and the subsequent management. We also review similar cases in the literature to understand their mechanism of asystole and the antecedent risk factors. In conclusion, when selecting a patient for VNS, all the possible risk factors for adverse cardiac events should be considered. Initial EKG Holter prior to implantation and periodic monitoring is recommended for patients on VNS. Plain Language Summary Vagal nerve stimulation (VNS) is a treatment used alongside medication for people with epilepsy who do not respond to drugs. It usually causes mild side effects such as cough or voice changes. Rarely, it can lead to serious heart problems such as slow heartbeat or heart stoppage, even years after the device is implanted. This report describes such a case in a 32‐year‐old patient and reviews similar cases to understand the risks. The authors recommend checking heart health with tests like an electrocardiogram before starting VNS and doing regular follow‐up checks to help prevent serious complications.